Black butler. XXVI - Toboso, Yana, 1984- (Yen Press, 2018)
While Earl Ciel Phantomhive, accompanied by his indomitable butler, Sebastian, is away on the trail of his quarry, Blavat, the sound of gunshots rends the silence of his London town house. A scene of carnage awaits master and servant upon their return, along with a chilling message from the forgotten past that shakes the young earl to his core...